The Fear of the Body of Voice - Franchi, Franca (Elephant & Castle, 2020)
At the intersection of various knowledges, the body of voice passes through time in unpredictable, contradictory ways, made up of often interrupted paths, certainly never linear. In this essay, I outline how the fear of the body of voice, while privileging alternative genealogies, submerged traditions, resurgences of images and their ability to prefigure the future, works on the materials of history, from literary texts to visual documents, from science to new technologies. The body of voice, medium of fear, is the focus of the essay, especially as for the classical tradition, the interweaving of magic, medicine, aesthetics, art and anthropology. Finally, the body of voice is considered for its aspects as a material object half simulacrum half fetish.